Intrauterine Device Use and Cervical Cancer Risk: A Systematic Review and Meta-analysis. Issue 3 (March 2018) - Cortessis, Victoria K.; Barrett, Malcolm; Wade, Niquelle Brown; Enebish, Temuulen; Perrigo, Judith L.; Tobin, Jessica; Zhong, Charlie; Zink, Jennifer; Isiaka, Vanessa; Muderspach, Laila I.; Natavio, Melissa; McKean-Cowdin, Roberta
Abstract : (Abstracted from Obstet Gynecol 2017;130:1226–1236) The third most common malignancy among women worldwide is cervical cancer. Control relies primarily on screening to detect premalignant cervical lesions, which is followed by their removal.